The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.17305/bjbms.2016.1497
|View full text |Cite
|
Sign up to set email alerts
|

Human epidermal growth factor receptor 2 (HER-2) status evaluation in advanced gastric cancer using immunohistochemistry versus silver in situ hybridization

Abstract: Accurate identification of human epidermal growth factor receptor 2 (HER-2) status in advanced gastric cancer patients is of utmost importance in terms of treatment planning. This study aimed to examine the HER-2 status in advanced gastric cancer patients using both immunohistochemistry (IHC) and silver in situ hybridization (SISH) techniques and to investigate concordance and diagnostic accuracy. In addition, associations between clinical parameters and HER 2 status were examined. A total of 313 patients diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…[6][7][8][9][10] The status of HER2 expression in gastric lesions is currently evaluated by immunohistochemistry (IHC), silver in situ hybridization (SISH), and fluorescence in situ hybridization (FISH). 5,11,12 It was found to be correlated with tumor grade and location on the intestine, but not with gender, age, tumor location or (tumor node metastasis) TNM stage, depth of invasion, lymph node metastases, and distant metastasis. 4,13 At present, gastroscopic biopsy is the main routine detection method to gain information about the histopathological characteristics of lesions before surgery.…”
Section: Introductionmentioning
confidence: 89%
“…[6][7][8][9][10] The status of HER2 expression in gastric lesions is currently evaluated by immunohistochemistry (IHC), silver in situ hybridization (SISH), and fluorescence in situ hybridization (FISH). 5,11,12 It was found to be correlated with tumor grade and location on the intestine, but not with gender, age, tumor location or (tumor node metastasis) TNM stage, depth of invasion, lymph node metastases, and distant metastasis. 4,13 At present, gastroscopic biopsy is the main routine detection method to gain information about the histopathological characteristics of lesions before surgery.…”
Section: Introductionmentioning
confidence: 89%
“…Human epidermal growth factor receptor 2 (HER-2), a member of the HER-2 family, is associated with an increased risk of recurrence and poor outcomes of certain malignancies, including breast and gastric cancer ( 13 ). HER-2 has been identified to be involved in cancer initiation and progression, and the dysregulation of HER-2 serves as an independent prognostic factor in gastric cancer ( 14 ). Thus, HER-2 is a common therapeutic target for gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…ERBB2, an oncogenic agent located in chromosome 17 (17q12–q21), encodes a 185-kDa transmembrane tyrosine kinase receptor (p185) [ 10 ]. ERBB2 has been identified to be implicated in cancerous initiation and progression, and its overexpression or amplification served as an independent prognostic factor in GC [ 11 ]. Furthermore, Tornillo et al revealed that ERBB2 overexpression activated the mammalian target of rapamycin (mTOR)/p70S6K signaling [ 12 ].…”
Section: Introductionmentioning
confidence: 99%